Aspects of waste heat recovery and utilisation (WHR&U) in pebble bed modular reactor (PBMR) technology - Senda, Franck Mulumba (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.